2002
DOI: 10.1103/physreve.66.017401
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the degree of polarization of the spectra from laser produced recombining Al plasmas

Abstract: Using a polarization-resolved UV-visible spectrometer, the degree of polarization of the spectra from laser produced Al plasmas was measured. The polarization resolution was achieved by using either a dichroic polarizer or a calcite crystal. The degree of polarization of Al III 4s(2)S(1/2)-4p(2)P(o)(3/2) transition at 569.66 nm was measured at different positions from a target surface. The degree of polarization was observed to be 2.1+/-0.13% at a distance of 220 microm from the target and decreased as the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 14 publications
3
32
0
Order By: Relevance
“…Therefore, the spatial structure may greatly affect their activities. Since Axelrod [7] suggested ideas of the PDG on a lattice, spatial prisoner's dilemma games (SPDG) have been extensively explored in various kinds of network models in the past few years, including regular lattices [8,9,10], random regular graphs [11], random networks with fixed mean degree distribution [12], small-world networks [13,14,15] and realworld acquaintance networks [16], etc. In the general SPDG, each agent can take one of two strategies (or states): cooperator (C) and defector (D).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the spatial structure may greatly affect their activities. Since Axelrod [7] suggested ideas of the PDG on a lattice, spatial prisoner's dilemma games (SPDG) have been extensively explored in various kinds of network models in the past few years, including regular lattices [8,9,10], random regular graphs [11], random networks with fixed mean degree distribution [12], small-world networks [13,14,15] and realworld acquaintance networks [16], etc. In the general SPDG, each agent can take one of two strategies (or states): cooperator (C) and defector (D).…”
mentioning
confidence: 99%
“…For convenience, following Refs. [10,11,14, 15], we set s = p = 0, r = 1, σ = 0.3, and 1 < t < 2. We define t − r as the relative temptation quantity (shortly RTQ) reflecting the extent of the temptation and cursorily partition the networks into three regions: lattice, small-world and random graphs corresponding to the variational range of Q: (0.0001, 0.001), (0.001, 0.3) and (0.3, 1) respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of the polarisation in this study was postulated to be an anisotropic electron distribution function caused by steep density gradients which result in polarized recombination radiation [6]. Similarly, studies on the visible emission from an Al plasma showed that the line emission can also be partially polarized [3]. In this study, the degree of polarisation in the Al 2+ doublet at 569.6 and 572.3 nm was found to be on the order of 3 %.…”
Section: Introductionmentioning
confidence: 66%
“…The technique of PPS has been applied to laser produced plasmas where partial polarisation has been observed in the x-ray and visible spectral ranges [2,3]. Importantly, a particular application of PPS known as polarisation-resolved laser induced breakdown spectroscopy (PRLIBS) exploits this partial polarisation in order to enhance the signal to background ratio over traditional LIBS measurements [4].…”
Section: Introductionmentioning
confidence: 99%